Asuhan Keperawatan Jiwa Pada Ny. W Dengan Masalah Utama Gangguan Konsep Diri: Harga Diri Rendah Akibat Skizofrenia Tak Terinci Di Ruang Dewaruci RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Lutfi Aulia; Titi Sri Suyanti (STIKES Columbia Asia Medan, 2026)
Background: Schizophrenia is a type of mental disorder that affects how sufferers behave, think, and feel. This condition can trigger nursing problems such as low self-esteem (harga diri rendah). In 2023, approximately 970 million people worldwide experience mental disorders, with schizophrenia prevalence in Indonesia reaching 3 per 1,000 households and in Central Java approximately 5.1% of households. Methods: This study used a descriptive approach in the form of a case study through the nursing process, including observation, interview, documentation study, and literature review. The general objective of this writing was to implement psychiatric nursing care for Ny. W with the main problem of Self-Concept Disorder: Low Self-Esteem Due to Undifferentiated Schizophrenia. Results: Nursing diagnoses that emerged were low self-esteem, social isolation, and self-care deficit. Interventions carried out included SP 1 and SP 2 for low self-esteem (HDR) and SP 2 for self-care deficit (DPD). Conclusion: After 4 days of nursing care on Ny. W according to the nursing action plan, the patient was able to establish a trusting relationship, identify positive abilities she possessed, perform chosen activities, and interact with her environment.